2018
DOI: 10.1007/s11325-018-1625-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between obstructive sleep apnea and non-alcoholic fatty liver disease: a systematic review and meta-analysis

Abstract: The relationship between obstructive sleep apnea (OSA) and non-alcoholic fatty liver disease (NAFLD) has been an issue of great concern. The primary purpose of this study was to determine the influence of OSA on the levels of liver enzymes including alanine transaminase (ALT) and aspartate transaminase (AST). The secondary purpose was to estimate the effect of OSA on the histological lesions of NAFLD, such as steatosis, lobular inflammation, ballooning degeneration, fibrosis, as well as NAFLD activity score (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…An increasing number of clinical studies point out to a potential link between obstructive sleep apnea (OSA), a respiratory disorder featured by nocturnal intermittent hypoxia (IH) and sleep fragmentation, and NAFLD (15)(16)(17)(18). To highlight, both OSA and NAFLD are especially prevalent among obese individuals and, more interestingly, the severity of nocturnal IH positively correlates with histological features of NASH in OSA patients (19).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of clinical studies point out to a potential link between obstructive sleep apnea (OSA), a respiratory disorder featured by nocturnal intermittent hypoxia (IH) and sleep fragmentation, and NAFLD (15)(16)(17)(18). To highlight, both OSA and NAFLD are especially prevalent among obese individuals and, more interestingly, the severity of nocturnal IH positively correlates with histological features of NASH in OSA patients (19).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a study has demonstrated that OSA patients were three times more likely to have NASH compared with subjects without OSA (41). Moreover, clinical evidence suggests a direct relationship between OSA and NAFLD severity (42,45). Interestingly, low O 2 saturation has been proposed as an important NAFLD risk factor in OSA patients: the lower the O 2 saturation, the higher the NAFLD severity (37,46).…”
Section: Clinical Evidences Linking Osa To Nafldmentioning
confidence: 99%
“…In addition, several other neurohormonal mechanisms are involved in the links between OSA and T2D, which are summarised in Fig. 3 (30,39,51,65,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113).…”
Section: Mechanisms: Osa Leading To Dysglycaemia and T2dmentioning
confidence: 99%
“…One plausible mechanism in patients with pre-diabetes or diabetes is autonomic neuropathy, which might impact on UA innervation (6), ventilatory drive and central respiratory responses to hypercapnia (109,110). In addition, T2D is associated with reduced pulmonary volumes and functions compared to healthy individuals which could affect UA stability (111,112,113,114,115,116,117,118,119,120,121) and diffusion capacity for carbon monoxide (112,113,122,123). The impact of T2D on the lungs seems to be related to the severity of hyperglycaemia independently of obesity and smoking (123), which raises the possibility that improvements in glycaemic control might have a favourable impact on OSA.…”
mentioning
confidence: 99%